Exploration of Multitarget Anti-Breast Cancer Potential of Selected Flavonoids Through Network Pharmacology and Molecular Docking - Dewanto, Nisriinaa Ayu; Nyratri, Btari Kalisha; Junus, Reneta Aisyah Maulina; Ismail, Dzava Prawinsyah Fairus; Hadisaputri, Yuni Elsa (Indonesian Journal of Biological Pharmacy, 2026)
Breast cancer remains a leading cause of mortality among women worldwide, including in Indonesia. Although current therapies such as chemotherapy, radiotherapy, and hormone therapy have improved patient outcomes, their effectiveness is frequently limited by systemic toxicity and multidrug resistance. In this study, the therapeutic potential of six natural flavonoid compounds was evaluated using a computational biology approach. Network pharmacology analysis identified estrogen receptor (ER-ɑ) (PDB ID: 3ERT), anti-apoptotic protein (BCL-2) (PDB ID: 6GL8), and DNA repair enzyme (PARP1) (PDB ID: 4R6E) as key molecular targets involved in breast cancer progression. The compounds were assessed through molecular docking, Lipinski’s Rule of Five, and absorption, distribution, metabolism, excretion, and toxicity (ADME-Tox) predictions to identify promising candidates with favorable pharmacokinetic and safety profiles. Among the evaluated compounds, rutin and kaempferol exhibited the most favorable overall characteristics based on binding affinity and predicted toxicity. These findings provide preliminary computational evidence supporting the potential of these flavonoids as lead candidates for further development. Nevertheless, experimental validation through molecular dynamics and biological studies is required to confirm their therapeutic relevance.